Targeting neuronal function for CNS drug discovery. (March 2017) - Hempel, Chris M.; Werley, Christopher A.; Dempsey, Graham T.; Gerber, David J.
Abstract : There is a pressing need for new and more effective treatments for central nervous system (CNS) disorders. A large body of evidence now suggests that alterations in synaptic transmission and neuronal excitability represent underlying factors for many neurological and psychiatric diseases. However, it has been challenging to target these complex functional domains for therapeutic discovery using traditional neuronal assay methods. Here we review advances in neuronal screening technologies and cellular model systems that enable phenotypic screening of neuronal function as a basis for novel CNS drug discovery approaches.